Analysis Of The Influence Of Rail Line On Railway Wheel Flens Wear - Akbar Zulkarnain; Dadang Sanjaya Atmaja; Daffa Ricta Ricardo; Andrew Joewono (Jurnal Syntax Transformation, 2023)
Ministerial Regulation number 175 of 2015 about Technical Specification Normal Speed Trains with Self-Propelling, the hardness rate of the train wheels must be lower than the hardness of the rail road. Trains operating at speeds of are considered as normal speed trains. Based on field observations, generally the flange is wear faster. In cases where flanges are wear out, the wheel’s flange must be to restored to its proper condition as long as the wheel diameter is still possible. This research was carried out by processing data using the Trend Linear and using the excel to get the results of a comparison of which wheels are faster to wear out on flange for each wheel in one train arrangement and which route causes wear out faster. Based on the data obtained, the Yogyakarta – Kutoarjo route traversed by An Electric-Diesel Locomotive Prambanan Express (Prameks) causes wear on flange than the Yogyakarta – Yogyakarta International Airport (YIA) route traversed by An Electric-Diesel Locomotive YIA and on the Solo – Wonogiri route traversed by An Electric-Diesel Locomotive Batara Kresna due to the total length of the mileage. and the longest total arc length of the two compared Lines. Meanwhile, the Solo – Wonogiri route traversed by An Electric-Diesel Locomotive Batara Kresna is ranked second in the cause of flange due to the smallest bend radius of the two compared lines. As well as the ranking of the last traffic that causes flange is the Yogyakarta - YIA.